2017
DOI: 10.1155/2017/1351945
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effect of Monochromatic Blue Light on Heat Stress Response in Commercial Broilers

Abstract: In a novel approach, monochromatic blue light was used to investigate its modulatory effect on heat stress biomarkers in two commercial broiler strains (Ross 308 and Cobb 500). At 21 days old, birds were divided into four groups including one group housed in white light, a second group exposed to blue light, a 3rd group exposed to white light + heat stress, and a 4th group exposed to blue light + heat stress. Heat treatment at 33°C lasted for five h for four successive days. Exposure to blue light during heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 62 publications
2
20
1
Order By: Relevance
“…Heat-stressed boldo-treated AA chicks exhibited a higher growth rate than even heat-stressed AV birds treated or not with boldo extract. Our results are consistent with those reported by Hascik et al [6] and Abdo et al [9].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Heat-stressed boldo-treated AA chicks exhibited a higher growth rate than even heat-stressed AV birds treated or not with boldo extract. Our results are consistent with those reported by Hascik et al [6] and Abdo et al [9].…”
Section: Discussionsupporting
confidence: 94%
“…The similar response of the antioxidant defense system of both strains to heat stress may be attributed to the large differences in gene expression of these enzymes. Abdo et al [9] reported that gene expressions of SOD and catalase in the liver of heat-stressed Ross and Cobb chickens were not significantly altered. Furthermore, the strong free radical scavenging and antioxidant activity of boldo leaves could be attributed to their high content of boldine and catechin [67].…”
Section: Discussionmentioning
confidence: 99%
“…Such increase indicates the activation of the pathways that are associated with counteracting the effects of oxidative stress. HS has been reported to increase the hepatic activity of CAT and SOD enzymes in two broiler chicken genotypes (Ross 308 and Cobb 500) (http://en.aviagen.com/brands/ross/products/ross-308) [67]. Habashy et al (2018) reported the up-regulation of the mRNA level of SOD (but not CAT) gene under chronic HS (12 days) [68].…”
Section: Stress-related Gene Expression Signaturesmentioning
confidence: 99%
“…Trial 5 was reared in spring, when the Texas climate experiences an increase in heat and humidity. Blue light has been shown to reduce measures of oxidative stress in heat-stressed broilers ( Abdo et al., 2017 ). Because plasma CORT also increases under heat stress ( Nelson et al., 2018 ) and increased plasma CORT can induce oxidative stress ( Lin et al., 2004 ), it would be expected that birds in the WS treatment would have lower plasma CORT concentrations compared to the WO treatment, even in warmer temperatures.…”
Section: Discussionmentioning
confidence: 99%